2021
DOI: 10.5194/soil-7-585-2021
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon mobility in equatorial podzols: soil column experiments

Abstract: Abstract. Transfer of organic carbon from topsoil horizons to deeper horizons and to the water table is still little documented, in particular in equatorial environments, despite the high primary productivity of the evergreen forest. Due to its complexing capacity, organic carbon also plays a key role in the transfer of metals in the soil profile and, therefore, in pedogenesis and for metal mobility. Here we focus on equatorial podzols, which are known to play an important role in carbon cycling. We carried ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
2
1
0
Order By: Relevance
“…Comparing both DOM types, the Peat is more aliphatic as indicated by the positive loadings of aliphatic products (C:0, C:1, Al1-3) and the alkyl side-chains on the PAHs and benzenes. The grouping of the B leachates negative on PyDim1 with the highest negative scores for the Water samples agrees with the fact that the source of SOM from hydromorphic Bh-horizons is mainly from processed DOM instead of in-situ deposited root material (Bardy et al, 2008;Lopes-Mazzetto, 2018a), and with a more proteinaceous DOM desorbed from B columns (Merdy et al, 2021). A larger homogeneity of the Stream samples is indicated by the more compact clustering compared to other DOM types.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 79%
“…Comparing both DOM types, the Peat is more aliphatic as indicated by the positive loadings of aliphatic products (C:0, C:1, Al1-3) and the alkyl side-chains on the PAHs and benzenes. The grouping of the B leachates negative on PyDim1 with the highest negative scores for the Water samples agrees with the fact that the source of SOM from hydromorphic Bh-horizons is mainly from processed DOM instead of in-situ deposited root material (Bardy et al, 2008;Lopes-Mazzetto, 2018a), and with a more proteinaceous DOM desorbed from B columns (Merdy et al, 2021). A larger homogeneity of the Stream samples is indicated by the more compact clustering compared to other DOM types.…”
Section: J O U R N a L P R E -P R O O Fsupporting
confidence: 79%
“…On the other hand, the presence of HA-Al-Si complexes suggested by our study is in agreement with the assumptions put forward to interpret the experiments of Merdy et al (2021). These authors showed, in laboratory column percolations of podzolic horizons, that certain types of organic matter can promote the transfer of Al and DOM through kaolinitic materials and presume the existence of DOM-Al-Si complexes.…”
Section: Implications In the Soil-water-plant Continuumsupporting
confidence: 92%
“…Although the depth of the direct influence by roots is limited to the extension of the root system, percolating DOM from upper soil horizons can transfer OC into much deeper soil regions. This depth migration is dependent of the water flow in the vadose zone and OC retention at mineral surfaces (Krettek & Rennert, 2021; McCarthy, 2005; Merdy et al., 2021), implying that soil texture can have a major influence on OC mobility.…”
Section: Introductionmentioning
confidence: 99%